KAJIAN STOK RAJUNGAN (Portunus pelagicus) DI PENDARATAN IKAN DESA BANCARAN BANGKALAN - Nur Dina Kamelia; Firman Farid Muhsoni (Jurnal Kelautan, 2020)
ABSTRACTBlue Swimming Crab (Portunus pelagicus) is an important commodity because it has high economic value and market demand both at home and abroad is still high. The higher demand for crabs for export makes the existence of crabs decrease. The purpose of this study is to assess the status of crab stocks (Portunus pelagicus) in the landing fish of Bancaran village, Bangkalan which includes growth rates, mortality, exploitation rates and recruitment patterns. This research was conducted in December 2019-February 2020. The small crab samples were caught by local fishermen using gill nets with a mesh size of 3.0-3.5 inches with a total sample of 624 in which 339 male crab and 285 females. The range of carapace widths is 5.24-13.83 cm which consists of 3 groups of sizes where as a whole the small crab in Bancaran Village, Bangkalan has an average carapace width ranging from 10.46 cm with a weight of 76.5 g. In general the growth patterns of male, female, and combined crabs are allometric negative (α, 0.05) with a growth equation Lt = 19.5 [1-e-0.11 (t - (- 0.5652))]. The natural mortality rate (M) of the crab is 0.49 per year and the catch mortality rate (F) is 0.40 per year, so that the crab exploitation rate (E) is known to be 45% (under fishing). The cradle recruitment pattern in the research location was the highest in June (17.77%).Keywords: Blue Swimming crab (Portunus pelagicus), Stock, Growth Rate, Mortality, Exploitation, RecruitmentABSTRAKRajungan (Portunus pelagicus) merupakan komoditas yang penting karena mempunyai nilai ekonomi tinggi dan permintaan pasar baik di dalam maupun luar negeri masih tinggi. Semakin tingginya permintaan akan rajungan untuk diekspor membuat eksistensi dari rajungan menjadi semakin menurun. Tujuan penelitian ini adalah mengkaji status stok rajungan (Portunus pelagicus) di pendaratan ikan desa Bancaran, Bangkalan yang meliputi laju pertumbuhan, mortalitas, tingkat eskploitasi dan pola rekrutmen. Penelitian ini dilakukan pada bulan Desember 2019-Februari 2020. Sampel rajungan yang ditangkap nelayan setempat menggunakan jaring insang dasar dengan mesh size 3,0-3,5 inci dengan total sampel berjumlah 624 ekor dimana 339 ekor rajungan jantan dan 285 ekor betina. Kisaran lebar karapas 5,24-13,83 cm yang terdiri atas 3 kelompok ukuran dimana secara keseluruhan rajungan di Desa Bancaran, Bangkalan memiliki rata-rata lebar karapas berkisar antara 10,46 cm dengan bobot 76,5 g. Secara umum pola pertumbuhan rajungan jantan, betina, dan gabungan adalah allometrik negatif (α, 0.05) dengan persamaan pertumbuhan Lt = 19,5 [1-e-0,11(t-(-0,5652))]. Laju mortalitas alami (M) rajungan sebesar 0,49 per thaun dan laju mortalitas penangkapan (F) 0,40 per tahun, sehingga diketahui laju eksploitasi rajungan (E) sebesar 45% (under fishing). Pola rekrutmen rajungan di lokasi penelitian tertinggi pada bulan Juni (17,77%).Kata kunci : Rajungan (Portunus pelagicus), Stok, Laju Pertumbuhan, Mortalitas, Eksploitasi, Rekrutmen